Simple and Robust GFAAS Methods for Determination of As, Cd, and Pb in Hemp Products Using Different Sample Preparation Strategies - Ribeiro Menezes, Iohanna M. N.; Nascimento, Patricia de A.; Gonzalez, Mario H. [UNESP]; Oliveira, Andrea (Springer Nature, 2021)
Hemp is one of the most complete plants for industrial and consumer purposes. In the food industry, the main hemp product is the seed oil, which contains a wide spectrum of compounds such as amino acids and fatty acids that are essential for human health. Given its growing consumption, systematic studies were undertaken for the quantification of toxic elements (As, Cd, and Pb) in hemp products, such as seeds (shelled and peeled), oil, protein, and butter. Factorial designs were used to optimize the sample preparation and instrumental conditions, resulting in robust analytical methods. For the toxicity assessment, the samples could be previously treated in either acid or alkaline medium, achieving limits of quantification of 0.6 μg g−1 (As), 0.04 μg g−1 (Cd) and 0.4 μg g−1 (Pb), and satisfactory values of accuracy (recoveries of 87–107%) and precision (relative standard deviation < 7%). The lead contents of hemp seeds were of concern (1.07–1.38 μg g−1), since they were above the established limits (0.2 μg g−1), while the cadmium levels could be considered safe. The As contents of the samples were all lower than the limit of quantification of the proposed method.
Keywords: Cannabis sativa L; Hemp; Sample preparation; Toxic elements